Chapter Algoritmi al lavoro. Riflessioni sul management algoritmico - BANO, Fabrizio (Firenze University Press, 2025)
The essay analyzes a specific characterisc of work managed through algorithms: in the absence offormalized, prescriptive and binding employer’s directives, the worker's performance is subject to an apparently spontaneous adjustment. The conditions that make this opaque form of self-conformation of the obligation are clarified, considering the algorithmic management work model and in light of the European discipline and of a reflection on the calculative and predictive power of the artificial intelligence, which this model uses.